2017
DOI: 10.1186/s12872-017-0724-x
|View full text |Cite
|
Sign up to set email alerts
|

Orthogonal P-wave morphology is affected by intra-atrial pressures

Abstract: BackgroundIt has previously been shown that the morphology of the P-wave neither depends on atrial size in healthy subjects with physiologically enlarged atria nor on the physiological anatomical variation in transverse orientation of the left atrium. The present study aimed to investigate if different pressures in the left and right atrium are associated with different P-wave morphologies.Methods38 patients with isolated, increased left atrial pressure, 51 patients with isolated, increased right atrial pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…In patients who underwent right heart catheterization for various reasons, it was demonstrated that elevated left atrial pressure was associated with abnormal P-wave morphology, while the patients with elevated right atrial pressure had normal P-wave morphology. 31 In our present study, there was also a relationship between the P-wave morphology variables and left ventricular mass, which has been shown to be a risk factor for SCD. 32 Significant correlations of the P-wave morphology parameters with LVMI, blood pressure, and LAD suggest that diastolic dysfunction may have contributed to the risk of cardiac death in the present study patients.…”
Section: Prognostic Significance Of P-wave Abnormalitiessupporting
confidence: 68%
See 1 more Smart Citation
“…In patients who underwent right heart catheterization for various reasons, it was demonstrated that elevated left atrial pressure was associated with abnormal P-wave morphology, while the patients with elevated right atrial pressure had normal P-wave morphology. 31 In our present study, there was also a relationship between the P-wave morphology variables and left ventricular mass, which has been shown to be a risk factor for SCD. 32 Significant correlations of the P-wave morphology parameters with LVMI, blood pressure, and LAD suggest that diastolic dysfunction may have contributed to the risk of cardiac death in the present study patients.…”
Section: Prognostic Significance Of P-wave Abnormalitiessupporting
confidence: 68%
“…Concurrent with these notions, in the present study, the values of the P‐wave morphology parameters were inversely associated with LVEF and directly associated with the left atrial size. In patients who underwent right heart catheterization for various reasons, it was demonstrated that elevated left atrial pressure was associated with abnormal P‐wave morphology, while the patients with elevated right atrial pressure had normal P‐wave morphology . In our present study, there was also a relationship between the P‐wave morphology variables and left ventricular mass, which has been shown to be a risk factor for SCD .…”
Section: Discussionmentioning
confidence: 93%
“…The first, premature atrial contraction, is characterized by normal ECG morphology with the preceding RR interval unnaturally short and followed by a pause. Premature ventricular contraction is characterized by a change in QRS morphology and enlarged P/T waves (P waves that are taller than normal (>2.5 mm to >0.25 mV) (Petersson et al 2017) or T waves with peaks larger than 5 mm (0.5 mV) (Levis 2015)).…”
Section: R Peak Detectionmentioning
confidence: 99%